Family therapy a constructive framework - Lowe, Roger D.
Roger Lowe introduces practitioners to the principles of using a constructive and collaborative approach with families. The approach builds on a strengths-based philosophy and focuses on enhancing family resilience and competence in a way that is both time-efficient and comprehensive